Leadership and entrepreneurship in the hospitality industry - Sheppardson, Chris; Gibson, Heather (Oxford, United Kingdom : Goodfellow Publishers Ltd., 2011)
Many aspire to be leaders and entrepreneurs where they can set the tone of business. This is particularly true in the hospitality industry where entrepreneurship is a dominant force, yet few people understand what it demands to be a leader in the sector.
1 Leadership; Never to be underestimated; Are managers becoming leaders?; Leadership in 2011; Leadership in the modern era; Leadership profiles and interviews; The changing face of hotel general management; -- 2 Entrepreneurship; Entrepreneurs profiles and interviews; Classic entrepreneurs; Corporate entrepreneurs; -- 3 Leaders and Entrepreneurs; The Entrepreneur; Leaders
Includes index.
Keywords: HOSPITALITY INDUSTRY -- MANAGEMENT